Sudocetaxel Zendusortide (TH1902) triggers the cGAS/STING pathway and potentiates anti-PD-L1 immune-mediated tumor cell killing - Demeule, Michel; Currie, Jean-Christophe; Charfi, Cyndia; Zgheib, Alain; Cousineau, Isabelle; Lullier, Véronique; Béliveau, Richard; Marsolais, Christian; Annabi, Borhane (Frontiers in Immunology, 2024)
The anticancer efficacy of Sudocetaxel Zendusortide (TH1902), a peptide-drug conjugate internalized through a sortilin-mediated process, was assessed in a triple-negative breast cancerderived MDA-MB-231 immunocompromised xenograft tumor model where complete tumor regression was observed for more than 40 days after the last treatment. Surprisingly, immunohistochemistry analysis revealed high staining of STING, a master regulator in the cancerimmunity cycle. A weekly administration of TH1902 as a single agent in a murine B16-F10 melanoma syngeneic tumor model demonstrated superior tumor growth inhibition than did docetaxel. A net increase in CD45 leukocyte infiltration within TH1902-treated tumors, especially for tumor-infiltrating lymphocytes and tumor-associated macrophages was observed. Increased staining of perforin, granzyme B, and caspase-3 was suggestive of elevated cytotoxic T and natural killer cell activities. Combined TH1902/anti-PD-L1 treatment led to increases in tumor growth inhibition and median animal survival. TH1902 inhibited cell proliferation and triggered apoptosis and senescence in B16-F10 cells in vitro, while inducing several downstream effectors of the cGAS/STING pathway and the expression of MHC-I and PD-L1. This is the first evidence that TH1902 exerts its antitumor activity, in part, through modulation of the immune tumor microenvironment and that the combination of TH1902 with checkpoint inhibitors (anti-PD-L1) could lead to improved clinical outcomes.